Optimizing Hospital Health Promotion Through Digital Educational Media in Tuban - Dwi Kurnia Purnama Sari; sugiyono; ilmiatus qoyimah; Adibah Enggar (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Hospital Health Promotion plays an important role in improving public health literacy and supporting preventive healthcare services. However, health promotion activities in several hospitals in Tuban are still predominantly conducted using conventional methods, resulting in limited effectiveness and accessibility of health information. This community service program aimed to optimize hospital health promotion through the utilization of digital educational media. The program was implemented using a participatory and educational approach involving healthcare workers, hospital health promotion staff, and hospital management. The activities consisted of preliminary assessment, development of digital educational media, training and mentoring sessions, implementation of digital health promotion, and evaluation. The digital media developed included educational videos, digital posters, social media content, and QR code–based educational materials. The results showed an improvement in participants’ knowledge and skills regarding the utilization of digital media for health promotion activities. Healthcare workers were able to develop and use digital educational content effectively within hospital services. Patients and visitors also demonstrated positive responses toward the use of digital educational media because the information was considered more attractive, interactive, and easier to access compared to conventional methods. In addition, digital media contributed to improving the consistency and efficiency of health education delivery in hospitals. In conclusion, optimizing hospital health promotion through digital educational media can enhance healthcare workers’ competencies, improve public access to health information, and support the improvement of healthcare service quality. Continuous training and institutional support are necessary to ensure the sustainability of digital-based health promotion programs in hospitals.